The New Opinion Leaders of Digital Marketing Era: Social Media Influencers - Taneri, Ecem (Journal of Applied And Theoretical Social Sciences, 2022)
The study examines the meaning of social media and social media influencers, penetration of social media platforms and the positioning of Instagram as a digital marketing tool. In this study, the growth of Instagram and influencer marketing are reviewed, how social media influencers and celebrities collaborate with brands and endorse them in social media platforms are approached. As a case study, digital marketing activities of four of the most preferred e-commerce platforms in Turkey have been examined during Black Friday; Trendyol, HepsiBurada, GittiGidiyor and Amazon. The reason why Black Friday, which is globally known as the opening day of shopping season, has been chosen as a case study is that retailers increase their digital marketing activities and market their sales on such special days. In this regard, the official Instagram accounts of the four noted e-commerce platforms have been analysed and Instagram posts with social media influencers and celebrity endorsement during Black Friday period have been studied. The study aims to contribute the literature by implying the usage of influencers by e-commerce platforms in terms of marketing perspective.